Przekształć wyrażenie na sume i wykonaj redukcje wyrazów podobnych.
d) (4x-7y-7)(-2)
e) -8(7n+9p+t)
f) -2(3a+1)+(4a-5)
g) 3(b-5a)-2(3b+a)
h) 5(2x+3y)-(x-2y)
i) 4(x/4+y/4)-5(3x/5-7y/5)
j) -6(3x/6-2y/6)+2/3(3x/2-6y)
proszę jak najszybciej to pilne :)

3

Odpowiedzi

2010-02-13T17:35:39+01:00
D) (4x-7y-7)(-2)
= (-2)*4x -2*(-7y) -2*(-7) =
= -8x +14y +14

e) -8(7n+9p+t)=
= - 56n -72p - 8t

f) -2(3a+1)+(4a-5)=
= -6a - 2 + 4a -5 =
= -2a -7

g) 3(b-5a)-2(3b+a)=
= 3b - 15a -6b -2a =
= - 6b - 17a

h) 5(2x+3y)-(x-2y)=
= 10x +15y -x + 2y =
= 9x + 17y

i) 4(x/4+y/4)-5(3x/5-7y/5)=
= x + y - 3x + 7y =
= - 2x + 8y

j) -6(3x/6-2y/6)+2/3(3x/2-6y)=
= -3x + 2y + x - 4y=
= - 2x -2y

4 5 4
2010-02-13T17:39:21+01:00
D) -8x+14y+14
e) - 56n-72p-8t
f)-6a-2+4a-5= -2a-7
g)3b-15a-6b-2a= -3b-17a
h)10x+15y-x+2y= 9x+17y
i)4x/4+4y/4-15x/5+35y/5=x+y-3x+7y= -2x+8y
j)-18x/6+12y/6+x-4y= - 3x+2y +x-4y= 4x-2y

proszę ;)
3 3 3
2010-02-13T17:53:31+01:00
D) (4x-7y-7)(-2) = -8x + 14y + 14

e) -8(7n+9p+t) = -56n - 72p -8t

f) -2(3a+1)+(4a-5) = -6a - 2 + 4a - 5 = -2a - 7

g) 3(b-5a)-2(3b+a) = 3b - 15a -6b -2a = -3b -17a

h) 5(2x+3y)-(x-2y) = 10x +15y - x + 2y = 9x + 17y

i) 4(x/4+y/4)-5(3x/5-7y/5) = x + y - 3x - 7y = -2x - 6y

j) -6(3x/6-2y/6)+2/3(3x/2-6y) = -3x + 2y + x - 4y = -2x -2y

POZDRAWIAM :))
4 4 4